Varietal turnover in potato and its effect on yield: Evidence from household surveys in India - Sharma, Kriti; Kumar, Anjani; Kumar, Nalini Ranjan (International Food Policy Research Institute, 2024)
Potato remains a crucial crop for achieving India’s food security goals and generating income for small-scale farmers. But India, the largest potato producer after China, remains behind many of its peers in attaining high yield. A low varietal replacement rate could be one of the major reasons for low yield in India. This critical issue warrants investigation, yet empirical results remain limited in the Indian context. Drawing on data from a comprehensive field survey of 892 potato growing farmers conducted in 2018–19 across five major potato-producing states in India, we find the determinants of the average area-weighted age of potato varieties used, and their impact on potato yield. The instrumental variable regression analysis establishes a negative association between varietal age and yield of potato. It also underscores the importance of access to weather forecast and linkages with agricultural organizations to achieve higher yield. Furthermore, it shows that household size, links to political party, and information about new seeds from friends, progressive farmers and input dealers are associated with lower varietal age. These insights will be instrumental for policymakers and potato breeders in promoting sustainable agricultural practices and boosting food security in India amidst the impending demographic challenges.